Immediate Correction of Idiopathic Scoliosis With Nighttime Braces Created by a Fully Automated Generative Design Algorithm: A Randomized Controlled Crossover Trial - Coulombe, Maxence; Guy, Aymeric; Joncas, Julie; Manitiu, Anton; Poirier, Philippe; Barchi, Soraya; Chémaly, Olivier; Brassard, Félix; Parent, Stefan; Labelle, Hubert; Aubin, Carl-Éric (Spine (Philadelphia, Pa. 1976), 2024)
Single-center, double-blinded, prospective crossover randomized controlled trial. To clinically validate the efficacy of nighttime braces designed automatically by a generative design algorithm to treat idiopathic scoliosis (IS). The tested hypothesis was the clinical equivalence of immediate in-brace correction for the new automatically generated brace design versus a standard Providence-type brace. Documented efficacy of brace treatment varies between centers, and depends on the empirical expertise of the treating orthotist. Our group previously developed a fully automated generative brace design algorithm that leverages a patient-specific finite-element model (FEM) to optimize brace geometry and correction before its fabrication. Fifty-eight skeletally immature patients diagnosed with IS, aged between 10 and 16 years were recruited. All patients received both a nighttime brace automatically generated by the algorithm (test) and a Providence-type brace designed by an expert orthotist (control). Radiographs were taken for each patient with both braces in a randomized crossover approach to evaluate immediate in-brace correction. The targeted 55 patients (48 females, 7 males) completed the study. The immediate Cobb angle correction was 57% 19 (test) versus 58% 21 (control) for the main thoracic (MT) curve, whereas it was 89% 25 (test) versus 87% 28 (control) for the thoracolumbar/lumbar (TLL) spine. The immediate correction with the test brace was noninferior to that of the Control brace ( P 0.001). The order in which the braces were tested did not have a residual effect on the immediate correction. The fully automated generative brace design algorithm proves to be clinically relevant, allowing for immediate in-brace correction equivalent to that of braces designed by expert orthotists. Patient 2 years follow-up will continue. This method's integration could help design and rationalize the design of braces for the treatment of IS. Level 2.